An Innovative Model of Occupational Structure: The GIG Economy - Dr. Manjeet Kaur; Dr. Harmeet Kaur; Dr. Aadil Hussain Mir (Journal of International Islamic Law, Human Right and Public Policy, 2025)
It has been observed that the twenty first century has brought about a paradigm shift in the structure of work due to globalization, the fast-growing wave of technological progress, and the alteration of the socio-economic frameworks. The emergence of the gig economy can be regarded as one of the most noticeable forms of this change. The gig economy calls into question traditional concepts of stable job, labor rights, and social protection, being characterized by short-term, flexible and task-based employment arrangements mediated by digital platforms to a large extent. This paper will look at the definition, nature, and the motivations behind the gig economy, discuss the benefits and issues of the gig economy, and assess how these factors relate to inequality and human development with specific reference to India. The research suggestion is supported by a qualitative and descriptive approach that relies on secondary sources and argues that the gig economy is improving flexibility, labor market participation, and economic efficiency but results in major issues concerning income insecurity, algorithmic control, and loss of labor protection. The paper ends with the conclusion that the answer to the questions of unbalanced regulatory frameworks should be to reconcile the goals of technological innovation to the tenets of decent work and inclusive development.